Genetic diversity and demographic instability in Riftia pachyptila tubeworms from eastern Pacific hydrothermal vents - Coykendall, D Katharine (BioMed Central, 2011)
BACKGROUND: Deep-sea hydrothermal vent animals occupy patchy and ephemeral habitats supported by chemosynthetic primary production. Volcanic and tectonic activities controlling the turnover of these habitats contribute to demographic instability that erodes genetic variation within and among colonies of these animals. We examined DNA sequences from one mitochondrial and three nuclear gene loci to assess genetic diversity in the siboglinid tubeworm, Riftia pachyptila, a widely distributed constituent of vents along the East Pacific Rise and Galápagos Rift. RESULTS: Genetic differentiation (F(ST)) among populations increased with geographical distances, as expected under a linear stepping-stone model of dispersal. Low levels of DNA sequence diversity occurred at all four loci, allowing us to exclude the hypothesis that an idiosyncratic selective sweep eliminated mitochondrial diversity alone. Total gene diversity declined with tectonic spreading rates. The southernmost populations, which are subjected to superfast spreading rates and high probabilities of extinction, are relatively homogenous genetically. CONCLUSIONS: Compared to other vent species, DNA sequence diversity is extremely low in R. pachyptila. Though its dispersal abilities appear to be effective, the low diversity, particularly in southern hemisphere populations, is consistent with frequent local extinction and (re)colonization events.